European structural funds to finance healthcare in Italian regions - Graps, Elisabetta A.; Lagravinese, Raffaele; Ruggiero, Adriano (Frontiers in Public Health, 2024)
In this work, we explore the extensive utilization of European Union Structural Funds to enhance regional healthcare systems in Italy over the period 2014–2020. These funds serve as vital instruments for financing the construction, renovation, and modernization of healthcare facilities, as well as supporting medical research and technological innovation. They enable the implementation of disease prevention and health promotion programs and provide essential income support to vulnerable families through the European Social Fund. Our analysis found that EU funding allocated to “health-related” projects during the 2014–2020 programming period, amounts to just over 6.19 billion euros [5.1 billion financed by the European Regional Development Fund (ERDF) and just over 1 billion financed by the European Social Fund (ESF)], of which 65.88% is funded by European resources. These funds supported a total of 26,739 projects, with 22,529 funded by the ERDF, primarily focusing on infrastructure projects and the acquisition of new technologies in the healthcare sector. Meanwhile, the 4,210 projects funded by the ESF were dedicated to personnel training and public health policies in the regions. The European co-financing provided by the ERDF exceeded 63%, while for the ESF, the European share was approximately 77%. Notably, some regions have leveraged these funds to pioneer telemedicine and healthcare technologies, improving healthcare accessibility, especially in remote areas. However, regional disparities in fund allocation and utilization persist and coordinated strategies and cross-regional collaboration, emphasizing the sharing of best practices and the reinforcement of transnational projects, need to successfully address these calls and to promote convergence not only in economic but also in healthcare terms.